2006
DOI: 10.1002/atr.5670400302
|View full text |Cite
|
Sign up to set email alerts
|

Train boarding and alighting rates at high passenger loads

Abstract: Line capacity in metro and high-frequency suburban railways is as much determined by station stop times as by factors such as line speed or train acceleration. This paper applies the method developed by London Underground to estimate the time that trains spend at stations, as a function of the physical characteristics of the situation (e.g. train door width) and the numbers of passengers involved. Analysis was carried out on a number of alternative designs for refurbishment of South West Trains' Class 455 inne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 2 publications
3
68
1
1
Order By: Relevance
“…With the mock-up car, the boarding and alighting time of the participants who play the role of passengers can be measured [5,6,16]. With this experimental simulation, the relations between the time and the influencing factors can be found.…”
Section: Methods Of Data Acquisitionmentioning
confidence: 99%
See 3 more Smart Citations
“…With the mock-up car, the boarding and alighting time of the participants who play the role of passengers can be measured [5,6,16]. With this experimental simulation, the relations between the time and the influencing factors can be found.…”
Section: Methods Of Data Acquisitionmentioning
confidence: 99%
“…Even though these benchmarking groups contain data from various continents, they do not have the Seoul metro data. Although Kim et al [17] found coefficients for the fractional model [16] suitable to the measured data in Korea, it is necessary to find more suitable model to the boarding and alighting time in Seoul.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Rolling stock plays a role in the problem of dwell time estimation due to many factors: the control system, number and width of doors [24], kind of service performed [25], horizontal and vertical gaps between the train and platform [26,27] and interior layout of the convoy seen as number and position of seats [28] or as passenger distance to exit doors and potential free space that the passenger is inclined to occupy [29]. As shown by [30], also fare collection methods may influence dwell times at stations.…”
Section: Introductionmentioning
confidence: 99%